2001
DOI: 10.1128/jvi.75.24.12121-12127.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Immunization of Wild-Type and Hepatitis C Virus Transgenic Mice Reveals a Hierarchy of Cellular Immune Response and Tolerance Induction against Hepatitis C Virus Structural Proteins

Abstract: To study the effect of genetic immunization on transgenic expression of hepatitis C virus (HCV) proteins, we evaluated the immunological response of HCV transgenic mice to HCV expression plasmids. FVB/n transgenic mice expressing HCV structural proteins (core, E1, and E2) and wild-type (WT) FVB/n mice were immunized intramuscularly with plasmids expressing core (pHCVcore) or core/E1/E2 (pHCVSt). After immunization, HCV-specific humoral and cellular immune response was studied. Both WT and transgenic mice immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 42 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…P7020.S expressing the core͞E1͞E2 polyprotein (amino acids 1-830) under the control of the cytomegalovirus promoter was constructed by cloning the same HCV cDNA from the bvHCV.S as described (18). Plasmid DNA was purified by using an endotoxin-free plasmid extraction kit (Qiagen, Valencia, CA) and dissolved in PBS at a concentration of 2 mg͞ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…P7020.S expressing the core͞E1͞E2 polyprotein (amino acids 1-830) under the control of the cytomegalovirus promoter was constructed by cloning the same HCV cDNA from the bvHCV.S as described (18). Plasmid DNA was purified by using an endotoxin-free plasmid extraction kit (Qiagen, Valencia, CA) and dissolved in PBS at a concentration of 2 mg͞ml.…”
Section: Methodsmentioning
confidence: 99%
“…Responder cells (3 Ï« 10 7 ) in 5 ml of CTM with 10% rat T-stim were cocultured with 10 g͞ml HCV core (amino acids 131-140, ADLMGYIPLV) or E2 (amino acids 614-622, RLWHYPCTI) peptide (18) in a six-well plate in a humidified incubator at 37°C, 5% CO 2 . Five days after stimulation, cytolytic activity of in vitrostimulated CTLs was measured by using a 6-h assay with 51 Crlabeled target cells.…”
Section: Ctl Assay and Intracellular Cytokine Staining (Ics)mentioning
confidence: 99%
“…It has been shown that DNA immunizations can induce both specific antibodies and cell-mediated responses against the structural and nonstructural (NS) HCV proteins in mice. [6][7][8][9][10][11][12][13][14][15][16] The NS protein 3 of HCV has been considered as a possible vaccine target. The reasons for this are that the NS3 protein shows a limited genetic variability, it performs multiple enzymatic functions, and it is a relatively large protein.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides were proposed by computer simulation (University of Wisconsin Genetics Computer Group (UWGCG), peptide structure program) and prepared by EMC microcollections (TĂŒbingen, Germany) with the following sequences: YQVRNSSGLYHVTNDCPNSS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), PGCVPCVREGNAS RCWVAVT (33-53), REGNASRCWVAVTPTVATRDGKL and PRRHWTTQDCNCSIYPG (104-120). Establishment and characterization of the stable transfected cell line expressing HCV core protein (SP2-19) and the control cell line SP2-0 have been described previously [34].…”
Section: Antigens and Cell Linesmentioning
confidence: 99%
“…induction of only borderline immunity after DNAimmunization or safety issues with viral vectors [15,16]. A number of different vaccine approaches have been investigated against HCV infection in the past like DNA vaccination [17][18][19], vaccination with recombinant proteins or peptides [11], vaccines based on virus-like particles [20] and viral or other pathogen vectors containing genetic information of HCV proteins [21].…”
Section: Introductionmentioning
confidence: 99%